Analysis of urban–rural differences in cognitive function among empty nest older adult in China based on Blinder-Oaxaca decomposition - Pan, Xiao; Zhang, Gui-Ning; Lai, Li-Chong; Zhang, Li-Yan; Huang, Hui-Qiao (Frontiers in Public Health, 2025)
ObjectiveThis study aims to explore the cognitive status and urban–rural differences of empty nest older adult in China, analyze in depth the possible reasons for these differences, and provide reference for developing targeted prevention strategies for the risk of cognitive impairment.MethodsA cross-sectional survey was conducted on empty nest older adult people from 35 cities and rural areas in 14 regions of Guangxi, China to evaluate their chronic disease prevalence, anxiety, depression, and cognitive status. The influencing factors and sensitivity of cognitive function impairment in empty nest older adult people in urban and rural areas were analyzed, and the Oaxaca Blinder decomposition method was used to analyze the urban–rural differences in cognitive function of empty nest older adult people.ResultsA total of 2083 empty nest older adult people were included, with a prevalence of the risk of cognitive impairment of 30.24%. Among them, the proportion of the risk of cognitive impairment was 33.33% (362/1086) in rural empty-nest older adult, higher than 26.88% (268/997) in urban empty-nest older adult. Older age, lower education level, and depression were common risk factors for cognitive impairment in both urban and rural empty-nest older adult (p < 0.05). Notably, rural empty-nest older adult showed sensitivity to the number of chronic illnesses and cervical and lumbar spondylosis. Among the differences in cognitive function among empty-nest older adult, 47.64% were related to the place of residence itself. Individual characteristic differences between urban and rural empty-nest older adult in education level (44.09%), number of chronic illnesses (27.74%), depression (15.75%), osteoporosis (10.79%), and age (6.19%) exacerbated the cognitive function differences.ConclusionThe proportion of the risk of cognitive impairment among empty nest older adult in rural areas is higher than that in urban areas, and education level is the most important factor affecting the difference in cognitive function between urban and rural areas. It is suggested to improve health education in rural areas, narrow the urban–rural gap in cognitive function of empty nest older adult, and promote fairness in medical service supply.